PERKEMBANGAN ILMU SYARAH HADITH: SUATU TELAAH RINGKAS - Ahmad Amir Nabil; Tasnim Abdul Rahman (RUSYDIAH: Jurnal Pemikiran Islam, 2021)
This paper discusses the development of science of hadith commentary since early century of Hijrah. It traces its historical development and instrumental role in expanding the dynamic understanding of hadith and its science. The paper attempts to illustrate the principle and discipline of usul al-sharh as set forth in the major works of hadith commentary underlying its principle, context and method. The discussion focusses on the method and approaches (ittijahat al-sharh) of traditionalist in interpreting and commenting the texts. The study is based on qualitative method in the form of library research, focusing on content analysis. The sources of documentation was primarily derived from traditional and classical works of hadith and contemporary references that provide extensive analysis of hadith commentary. The study found that the science of hadith commentary was originated in the classical and medieval hadith works that extensively articulated its rigorous and underlying principle. This tradition was continued in modern context in the highly authoritative works of hadith commentary that brought forth modern and contextual approaches in analyzing hadith texts.